PERLINDUNGAN HUKUM TERHADAP PELAKU TINDAK PIDANA KORUPSI DALAM PELAKSANAAN PERAMPASAN ASET SECARA TIDAK WAJAR DIKAITKAN DENGAN ASAS PRADUGA TAK BERSALAH - Kevin Kaleb Panjaitan; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Provisions regarding confiscation of assets resulting from criminal acts of corruption are regulated in Article 18 paragraph (1) of Law Number 31 Year 1999 jo. Law Number 20 Year 2001 Concerning the Eradication of Corruption Crime. In implementing the law enforcement apparatus will be faced with various conditions that lie in the protection of human rights, namely the rights of the suspect or the rights of the defendant, in realizing the due process of law, law enforcers must pay attention to the rights of the suspect or defendant which normatively must be have a place in the criminal justice system. However, this mechanism of expropriation without criminal charges which is considered a breakthrough contains a very crucial point. The application of the presumption of innocence must be applied by the KPK in confiscating assets resulting from criminal acts of corruption during the investigation stage. The KPK is not allowed to seize without first tracing and identifying assets. However, in fact, in some cases the plunder was carried out improperly. The confiscation of assets must be carried out by the KPK through a quality control assessment. The existence of this control is an important part so that confiscation is carried out carefully and thoroughly. The KPK is obliged to apply the presumption of innocence to assets owned by perpetrators of corruption. Applying the principle of presumption of innocence in confiscation of assets is an effort to provide legal protection and avoid confiscating assets by violating the protection of property rights.This research will be compiled using the juridical normative research type, which is research that is focused on examining the application of legal principles or norms to legal principles. By conducting identification in advance of the legal principles that have been formulated in certain legislation. The data collection technique used in this research is literature study. The approach used in this research is to use a normative approach, namely literature law research.The results of the research conducted by the author are first, the arrangement of improper confiscation of assets against perpetrators of corruption in Indonesia in Law No. 31 of 1999 jo. Law Number 20 Year 2001. The regulation stipulates that confiscation of assets without punishment can be carried out if the judge first grants a civil suit from the state attorney or agency that is injured, namely in the absence of sufficient evidence to continue the criminal process. The form of legal protection for perpetrators of corruption is linked to the presumption of innocence. Protection of Human Rights of Suspects is protected in the constitution and laws in force in Indonesia. The 1945 Constitution (UUD) is the basis for all Indonesian citizens to exercise their rights as citizens in the life of the nation and state.Keywords: Plunder - Corruption - Presumption of Innocence